Renaissance perspectives in literature and the visual arts - Roston, Murray (Princeton legacy library, 1987)
Roston demonstrates that what emerges is not a fixed or monolithic pattern for each generation but a dynamic series of responses to shared challenges. The book relates leading English writers and literary modes to contemporary developments in architecture, painting, and sculpture, exploring by a close reading of the texts and the artistic works the insights such comparison offers. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.